FROM OFFICIAL SPEECH TO PUBLIC EMOTIONS: A PRAGMATIC DISCOURSE ANALYSIS IN POLITICAL COMMUNICATION - Mubarok, Yasir; Budiono, Taat (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
In today’s political communication, spontaneous statements by public officials spread quickly through digital media and strongly influence public opinion. Because these statements are produced without careful preparation, they often trigger intense emotional reactions and public polarization. However, systematic linguistic research on this phenomenon, especially in the Indonesian context, remains limited. The present research aims to examine the forms of speech acts in spontaneous political utterances, the patterns of public response they generate, and the sociolinguistic contexts that shape their interpretation. This study uses a qualitative approach with pragmatic discourse analysis, integrating Austin’s (1962) and Searle’s (1969, 1979) speech act theory, stance detection for public response analysis (ALDayel & Magdy, 2021), and Hymes’ (1974) Speaking model in a three-stage framework. This combination enables simultaneous examination of linguistic structures and sociolinguistic contexts. Data were drawn from ten unplanned statements by the Regent of Pati, Central Java, Indonesia, during a doorstop interview, recorded and shared via the official YouTube channel. Findings show the speech acts comprised directives (50%), commissives (40%), and representatives (10%). Directives, often challenging or commanding in a provocative tone, were the main triggers for criticism (67.7%) and sarcasm (6.1%) on social media. Commissives, emphasizing an uncompromising stance, strengthened perceptions of resistance to dialogue and mobilized regional opposition (26.2%). Representative acts, framed as claims “for the people,” failed to mitigate criticism and instead raised debates on credibility. Stance detection revealed polarization: 67.7% of responses fell into the Against category, 26.2% indirectly aligned with Favor toward opposition movements, and 6.1% employed sarcasm or humor as symbolic resistance. No neutral or purely informative responses were found. Hymes’ Speaking model identified contextual amplifiers, including the interview’s confrontational setting, direct targeting of individuals, and rapid digital dissemination, which intensified virality and polarization. The absence of diplomatic political language, despite formal freedom of expression, contributed to perceptions of arrogance. Overall, the study demonstrates that the form, tone, and context of spontaneous political speech acts significantly shape public responses. Provocative directives and rigid commissives escalate polarization, while unsupported representative claims fail to restore credibility. The implication is that public officials need to communicate in a more convincing, open, and careful manner, as well as pay attention to the long-term impact of their choice of words, tone, and media used, especially in an era of openness and rapid flow of information on social media.